Adaptação transcultural e avaliação das propriedades psicométricas da falls efficacy scale international: um instrumento para avaliar medo de cair em idosos - Flavia Fernandes Oliveira Camargos (2007)
Objective: To assess the cross-cultural and psychometric properties of Falls Efficacy Scale International (FES-I) in a Brazilian community with an elderly sample. Method: As recommended by the Prevention of Falls Network Europe, the instrument was culturally adaptated for the Brazilian population sample. The FES-I was administered in conjunction with other variables (depression; functional parameters; demographic and clinical data; history of falls; level of health and physical activity and fear of falling). These measures were applied to 163 community elderly (73.4±5.5 years; 77.9% female) to verify the instruments psychometric properties. From this group, a randomized sample of 58 subjects was selected for the reliability tests. Descriptive statistics were used for all variables along with non-parametric tests to analyze the distribution of FES-Is total score and the others variables, with a significance level of 0.05. To verify reliability and internal consistency the intra-class correlation coefficient (ICC) and Cronbachs alpha () were used, respectively. Results: The results revealed that indices of internal consistency was = 0.93 and intra- and inter-reliability were 0.84 and 0.91, respectively. There were significant association between the FES-I total score and the history of falls and levels of fear of falling and with all of the cathegorical variables, except for age and medications used. Conclusions: After the cross-cultural adaptation and the sample assessment, the FES-I showed to be appropriate to evaluate fear of falling in a Brazilian community of elderly individuals.